Complete blood collection‐based systemic inflammation biomarkers for patients with hidradenitis suppurativa. (7th May 2022) - Gambichler, T.; Hessam, S.; Cramer, P.; Abu Rached, N.; Bechara, F.G.
Abstract: Background: Hidradenitis suppurativa (HS) is a relatively common chronic inflammatory condition of intertriginous skin. In recent years, the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR) and platelet/neutrophil ratio (PLR) have been shown to be indicators of systemic inflammation correlating with severity of inflammatory conditions. Objectives: We aimed to analyse for the first time the systemic inflammation biomarkers also including the pan‐immune‐inflammation value (PIV) and the systemic immune‐inflammation index (SII) in HS patients and controls. Methods: This study retrospectively investigated clinical and laboratory data of 142 patients with HS. Moreover, a sex‐age‐matched healthy control group was included. The severity of HS was routinely assessed by the Hurley staging, the mHSS and the SAHS score. All inflammation‐based biomarkers were calculated from absolute values of complete blood counts. Receiver‐operating characteristics analyses, including the Youden index, were performed in order to determine optimal cut‐off values and test performance. Results: Whereas PIV and SII were significantly higher in HS patients, PLR, MLR and PNR were significantly lower in HS patients when compared to controls. Almost all inflammation‐based biomarkers significantly correlated with disease severity. However, PIV was the only test that was significantly associated with HS severity as indicated by a Youden index of 0.56 (associated criterion: 756.4; AUC: 0.79, P  < 0.0001). Conclusions: Although all systemic inflammation‐based biomarkers investigated are more or less associated with HS severity, the PIV appears to have the best performance in this regard. It may be employed in adjunction with the clinical scores for treatment decision making or clinical trial assessments.